Pharmacodynamic Interaction of Fenugreek Seeds Extract with Fluvastatin in Diabetes Induced Vascular Dysfunction - kumar, Shankul (International Journal of Pharmaceutical & Biological Archive, 2012)
Pharmacodynamic Interaction of Fenugreek Seeds Extract with Fluvastatin in Diabetes Induced Vascular Dysfunction